Mainlobe jamming suppression for distributed radar via joint blind source separation. Issue 7 (1st July 2019) - Ge, Mengmeng; Cui, Guolong; Kong, Lingjiang
Abstract : In the presence of the mainlobe jamming, the performance of the modern radar system would degrade significantly, i.e. increasing probabilities of false alarm and loss detection. In this study, the authors consider the jamming suppression problem in noise environment for the distributed radar with single transmitter and multiple receivers, where the multiple jammings enter into all the receivers through the main beam of the antennas. A framework based on joint blind source separation (JBSS) is proposed. First, the signal model accounting for both the target and jammings is developed. Second, the target and the jamming signals are separated by exploiting the generalised non‐orthogonal joint diagonalisation JBSS method. Then, the separated target signals are employed to find the target location with the elliptic location method. Finally, they assess the performance in noise environment by numerical simulations, and the results show that the proposed algorithm can suppress successfully quite a lot different kinds of jamming signals, e.g. the noise‐modulated and the digital radio‐frequency memory jammings.